2020
DOI: 10.3892/mmr.2020.10920
|View full text |Cite
|
Sign up to set email alerts
|

Combining antioxidant astaxantin and cholinesterase inhibitor huperzine A boosts neuroprotection

Abstract: oxidative stress is a pathophysiological condition resulting in neurotoxicity, which is possibly associated with neurodegenerative disorders. in this study, the antioxidative effects of the antioxidant astaxanthin (aXT) in combination with huperzine a (Hupa), which is used as a cholinesterase inhibitor for the treatment of alzheimer's disease, were investigated. Pc12 cells were treated with either tert-butyl hydroperoxide (TBHP), or with the toxic version of β-amyloid, aβ 25-35 , to induce oxidative stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…HupA inhibits the cytoplasmic translocation of CytoC and caspase-3 cleavage [69], attenuating apoptotic-inducing signals (see Table 2), and possibly prevents APP-induced mitochondrial dysfunction by reversing the disruption of NIPSNAP1 protein localization in the mitochondrial matrix [37]. HupA also upregulates glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), and catalase (CAT), thus preventing oxidative stress [70]. HupA mediated neuroprotection possibly involves restoration of an intact double membrane, which restores the membrane potential and ATP production, meaning preserved energy homeostasis [35,52] (see Table 2).…”
Section: Neuroprotective Molecular Signaling Of Hupa Against Admentioning
confidence: 99%
“…HupA inhibits the cytoplasmic translocation of CytoC and caspase-3 cleavage [69], attenuating apoptotic-inducing signals (see Table 2), and possibly prevents APP-induced mitochondrial dysfunction by reversing the disruption of NIPSNAP1 protein localization in the mitochondrial matrix [37]. HupA also upregulates glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), and catalase (CAT), thus preventing oxidative stress [70]. HupA mediated neuroprotection possibly involves restoration of an intact double membrane, which restores the membrane potential and ATP production, meaning preserved energy homeostasis [35,52] (see Table 2).…”
Section: Neuroprotective Molecular Signaling Of Hupa Against Admentioning
confidence: 99%
“…This result is in agreement with a previous in vitro study. 22 Additionally, the results of the current research showed that AST demonstrated potent antiinflammatory properties. It inhibited the development of pro-inflammatory mediators such as TNF-α and IL-6, which were increased by scopolamine injection.…”
Section: Histological Examination Of Brain Tissuesmentioning
confidence: 63%
“…Additionally, HupA activates the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX), avoiding oxidative stress. (35). The reconstruction of an intact double membrane, which restores the membrane potential and ATP generation, implying preserved energy balance, may play a role in HupAmediated neuroprotection.…”
Section: IVmentioning
confidence: 99%